Preparation method of low-temperature carbon-coated γ-MnO2 and aqueous zinc ion battery
Through the preparation method of low-temperature carbon coating γ-MnO2, two-stage temperature-raising treatment and low-temperature decomposition of organic carbon sources are used to solve the problem of γ-MnO2 changing crystal form in heat treatment, and the stability of its structure and battery performance are improved.
Patent Information
- Application Number
- CN202510223729.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-27
AI Technical Summary
In heat treatment or sintering methods, the crystal form of γ-MnO2 material is prone to change, resulting in unstable structure during carbon coating and it is difficult to keep the γ-phase structure unchanged.
The preparation method of low-temperature carbon coating γ-MnO2 is adopted. Through two sections of temperature-raising treatment, the first section is heated to 180-200℃, and the second section is heated to 280-320℃, and the temperature is constant at this temperature for 1-3 hours. Carbon coating is performed using low-temperature decomposition organic carbon sources such as corn flour, starch, citric acid or glucose.
The crystal structure of γ-MnO2 is effectively maintained and its high discharge capacity and charge and discharge cycle stability in aqueous zinc ion batteries are achieved.
Smart Images

Figure CN119725504B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a preparation method of low-temperature carbon-coated γ-MnO2 and an aqueous zinc ion battery. Background Art
[0002] MnO2 has been widely used as a cathode material for aqueous zinc-ion batteries in recent years due to its abundant materials, low price, high theoretical capacity, environmental friendliness and good safety. However, MnO2 materials have poor electronic / ionic conductivity, low reversible discharge capacity and rate performance, and poor cycle stability, which restricts their widespread application in aqueous zinc-ion batteries. In order to solve the problems of MnO2 conductivity and electrochemical properties, researchers have proposed a variety of performance optimization strategies and improvement methods, such as 1) metal cation / transition metal ion pre-embedding method (Adv. Mater. 2020, 32:2002450); 2) coating MnO2 materials with organic conductive polymers; 3) composite with polyaniline and coating with carbon materials. For example, MnO2 materials coated with graphene scrolls can promote charge transfer and reduce stress to inhibit the collapse of the MnO2 material structure ( ACS Appl. Mater. Interfaces 2022, 14, (20): 23022-23032). However, the method of coating with graphene scrolls is costly and not conducive to industrialization. Journal of Materials Research 2019, 33:530 reported that γ-phase MnO2 was synthesized using potassium permanganate and manganese sulfate as raw materials, and glucose was used as carbon raw material to prepare MnO2 / C composite material by liquid phase sintering carbon coating. The composite material obtained by coating with this method changed the original manganese dioxide crystal structure, causing the manganese dioxide structure to change from γ phase to α phase, and failed to make the γ-phase crystal form stable.
[0003] MnO2 has many crystal forms such as α-MnO2, β-MnO2, γ-MnO2, δ-MnO2 and λ-MnO2. The chemical compositions of different crystal forms of MnO2 are basically the same, but they show great differences in performance. Studies have found that γ-MnO2 has high electrochemical activity in aqueous batteries, and its performance is better than that of various crystal forms. It is the most widely used electrode material in the battery industry. However, the thermal stability of γ-MnO2 is worse than that of α-MnO2 and β-MnO2, and it will begin to change its crystal form at 300-350℃. Our research found that during the process of carbon coating and heat treatment of MnO2 surface, if low temperature is used to decompose organic carbon sources such as glucose, citric acid and other substances, the reducing agent substances produced by thermal decomposition contain rich gases such as carbon monoxide and aldehydes. These gas substances can reduce MnO2 to produce Mn3O4, resulting in the phase change of γ-MnO2. If a high molecular weight organic polymer carbon source such as polyaniline, dopamine, thiophene and the like is used, it is often necessary to heat it at high temperatures (500-900 oC) Sintering and carbonization treatment: high temperature treatment makes the γ-MnO2 crystal form very easy to change, so the existing technology cannot ensure that the crystal structure of γ-MnO2 remains unchanged before and after heat treatment and carbon coating. Therefore, when using heat treatment or sintering method to carbon coating γ-MnO2, how to effectively stabilize the γ-phase structure of MnO2 and ensure that it does not undergo crystal transformation is a problem worthy of key research. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing low-temperature carbon-coated γ-MnO2 and an aqueous zinc ion battery in view of the deficiencies in the prior art.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing low-temperature carbon-coated γ-MnO2 comprises the following steps:
[0007] Take γ-MnO2 powder and organic carbon source compound and mix them;
[0008] The obtained mixed material is subjected to two-stage temperature rising treatment. The first stage of temperature rising is controlled at a temperature range from room temperature to T1, where T1 is 180-200°C. The second stage of temperature rising is controlled at a rate of 0.1-1.0°C / min, and the temperature range is from T1 to T2, where T2 is 280-320°C. The mixed material is subjected to a constant temperature treatment at T2 for 1-3 hours, and then naturally cooled to room temperature to obtain carbon-coated MnO2, wherein MnO2 is γ-phase.
[0009] In the above technical solution, further, the organic carbon source compound is selected from low-temperature decomposition organic carbon sources, which can usually be one or more of corn flour, starch, citric acid, and glucose.
[0010] Furthermore, the particle size of the γ-MnO2 powder is usually less than 38 microns, which is more conducive to ensuring the electrochemical activity of the electrode in subsequent applications.
[0011] Furthermore, the weight ratio of the organic carbon source compound to the γ-MnO2 powder is 1-10:15.
[0012] Furthermore, the mixing is solid-solid phase mixing or liquid-solid phase mixing.
[0013] When solid-solid phase mixing is adopted, the mixture may be stirred or mechanically mixed by roller mixer, or placed in a ball mill and dry-milled with ceramic balls 10 times the mass of the material, preferably at a speed of 200-300 r / min for 2-20 h, more preferably for 5-10 h.
[0014] When liquid-solid phase mixing is adopted, the organic carbon source compound can be dissolved in distilled water at a concentration of 50-500 g / L, preferably 100-350 g / L. The γ-MnO2 powder is poured into the prepared carbon source compound aqueous solution, and mixed and stirred evenly, and then slowly evaporated at a temperature of 40-80°C, preferably 50-60°C, to a semi-dry state or a dry solid state.
[0015] Furthermore, the temperature raising treatment can be carried out in a tubular furnace or a muffle furnace. The atmosphere of the tubular furnace is oxygen or nitrogen, the flow rate is 20-100 ml / min, and the preferred flow rate is 50-70 ml / min. The atmosphere of the muffle furnace is air, and the holes are opened for inlet and outlet gas flow. More preferably, the tubular furnace and the muffle furnace have an exhaust system.
[0016] Furthermore, the first stage heating rate may be 5-10° C. / min.
[0017] Furthermore, the second stage heating rate is 0.1-0.5°C / min.
[0018] Furthermore, during the second stage of heating and constant temperature treatment, the reaction system is evacuated or gas is introduced for exhaust treatment, so as to discharge the decomposition gas generated during the heat treatment from the reaction system as much as possible.
[0019] A MnO2 electrode slurry contains carbon-coated MnO2 prepared as described above.
[0020] An aqueous zinc ion battery, wherein the positive electrode of the battery contains the electrode slurry as described above.
[0021] The two-stage heating treatment method used in the present invention is crucial, because the low-temperature decomposition of organic carbon sources is used for carbon coating. These organic carbon sources will decompose to produce reducing substances such as CO and aldehydes when they are above 200°C. If they fully contact and react with MnO2, Mn3O4 will be generated. Therefore, during the treatment process, the system temperature needs to be controlled as low as possible below the decomposition temperature of the organic carbon source during the first stage of heating, and after the system temperature reaches nearly the decomposition temperature of the organic carbon source, the heating rate is accurately controlled to avoid heating too fast, so that the reducing substances such as CO and aldehydes produced by decomposition can be discharged out of the furnace in time when the concentration is not high, or the decomposed reducing substances can be quickly discharged under the conditions of exhaust or exhaust. Through this treatment, it is effectively achieved to maintain the γ crystal form of MnO2 while carbon coating it.
[0022] The present invention has at least the following beneficial effects:
[0023] The technical solution of the present invention can realize carbon coating of γ-MnO2 material while keeping the crystalline structure unchanged, thus overcoming the difficulty in the prior art in that γ-MnO2 is prone to phase change during heat treatment and carbon coating.
[0024] The aqueous zinc ion battery composed of the positive electrode composed of carbon-coated γ-MnO2 and the negative zinc electrode assembled by the technical solution of the present invention has high discharge gram capacity and charge-discharge cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of MnO2 powder samples before and after carbon coating.
[0026] Figure 2 Scanning electron microscope (SEM) image of carbon-coated MnO2 sample.
[0027] Figure 3 , Figure 4 , Figure 5 , Figure 6 For the four selected areas of manganese dioxide particles (such as Figure 2 (shown) Element energy spectrum analysis results.
[0028] Figure 7 EDAX large-area analysis results of manganese dioxide particles after carbon coating.
[0029] Figure 8 XRD patterns of MnO2 powder samples before and after carbon coating.
[0030] Fig. 9 Effect of heating rate on the crystal structure of MnO2 during carbon coating.
[0031] Fig.10 Effects of two concentrations of glucose solution on the crystal structure of MnO2 after carbon coating.
[0032] Fig.11 XRD patterns of glucose, starch and corn flour after carbonization at 300 °C.
[0033] Fig.12 SEM photo of the surface of manganese dioxide particles after coating.
[0034] Fig.13 Comparison of the cycling stability of γ-MnO2 electrode after carbon coating and its performance before carbon coating.
[0035] Fig.14 X-ray diffraction pattern of γ-MnO2 before and after carbon coating.
[0036] Fig.15 EDAX spectrum analysis of the carbon-coated γ-MnO2 sample showed that it contained carbon in addition to manganese and oxygen.
[0037] Fig.16EDAX energy spectrum analysis showed that the outermost layer of γ-MnO2 after carbon coating contained only carbon element and the carbon layer was about 50-100 nanometers thick.
[0038] Fig.17 Comparison of electrochemical cycling stability of γ-MnO2 electrode before and after carbon coating.
[0039] Fig.18 X-ray diffraction pattern of γ-MnO2 before and after carbon coating.
[0040] Fig.19 X-ray diffraction pattern of γ-MnO2 before and after carbon coating.
[0041] Fig. 20 X-ray diffraction pattern of γ-MnO2 before and after carbon coating.
[0042] Fig.21 Comparison of electrochemical cycling stability of electrodes with different physical phase structures. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and some preferred embodiments of the present invention.
[0044] According to one embodiment of the present invention, the γ-MnO2 powder is not carbon-coated by the method of the present invention and applied to an aqueous zinc ion battery, which specifically includes the following:
[0045] Step 1: Select commercial electrolytic γ-MnO2 powder as the active material, and sieve the γ-MnO2 powder with particles less than 38 microns through a 400-mesh sieve. Select 904L stainless steel mesh as the positive current collector, and use it for standby after ultrasonic cleaning, degreasing, and drying.
[0046] Step 2, weigh a certain amount of carbon source fine powder compound such as corn flour, starch, citric acid, glucose or a mixture thereof, and mix it with the γ-MnO2 in step 1 in a solid-solid phase or a liquid-solid phase. If solid-solid phase mixing, the carbon source compound and γ-MnO2 are stirred and mixed evenly at a weight ratio of 1-10:15 or mixed evenly with a mechanical roller mixer or put into a ball mill and dry-milled and mixed evenly with ceramic balls of 10 times the mass of the material, and ball milled at a speed of 200-300r / min for 2-20h, preferably 5-10h. If liquid-solid phase mixing, weigh a certain amount of carbon source compound and dissolve it in distilled water at a concentration of 50-500 g / L, preferably 100-350g / L. Pour the γ-MnO2 powder screened in step 1 into the prepared carbon source compound aqueous solution, mix and stir evenly, and then slowly evaporate the water at a temperature of 40-80°C, preferably 50-60°C, to a semi-dry state or a dry solid state.
[0047] Step 3, transfer the mixed material obtained in step 2 to a ceramic crucible, and place the ceramic crucible in a tube furnace or a muffle furnace. The atmosphere of the tube furnace is oxygen or nitrogen, with a flow rate of 20-100 ml / min, preferably a flow rate of 50-70 ml / min, and the atmosphere of the muffle furnace is air, with holes for inlet and outlet or ventilation for exhaust or pumping flow. The first stage heating rate is 5-10 ° C / min, and the temperature range is from room temperature to 180-200 ° C. The second stage heating rate is 0.1-1.0 ° C / min, preferably a heating rate of 0.1-0.5 ° C / min, and the temperature range is from 180-200 ° C to 280-320 ° C. And keep the temperature at this temperature for 1-3 hours, preferably 2 hours. Then cool from the second stage temperature to room temperature, and the cooling rate is natural cooling. More preferably, the reaction system is evacuated or exhausted during the second stage heating process and / or the constant temperature treatment process.
[0048] Step 4, preparation of MnO2 electrode slurry. Grind the manganese dioxide / carbon composite obtained in step 3 above and weigh 75-85wt% electrode material weight ratio, add 6-10wt% acetylene black and 1-5wt% carbon nanotubes (aqueous solution), mix well and pour into a ball mill, then weigh and add ceramic balls 10 times the mass of the electrode material for wet grinding, and ball mill at a speed of 200-300r / min for 2-20h, preferably 5-10h. After evaporating part of the water in the obtained mixed slurry, add an appropriate amount of anhydrous ethanol and 5-9wt% binder (PTFE suspension), stir the slurry into a paste-like mud mass under constant stirring and set aside.
[0049] Step 5, preparation of MnO2 electrode. The MnO2 paste prepared in step 4 is rolled into uniform thin sheets on a biaxial rolling machine for multiple times, and the stainless steel mesh prepared by cleaning and degreasing in step 1 is added and rolled together for multiple times, and the total thickness of the final electrode is 0.40-0.60 mm. After completion, the electrode is placed in a vacuum drying oven at 80-200°C, preferably at a temperature of 120-150°C, and the drying time is 1-3 hours. After drying, weigh and measure the electrode thickness and MnO2 loading. The electrode thickness is preferably 0.50-0.55 mm, and the MnO2 loading is 35-50 mg / cm 2 , preferably 40-45 mg / cm 2 .
[0050] Step 6, battery assembly and performance testing. The battery performance is measured by the constant current charge and discharge (GCD) method. The positive electrode, the separator and the negative electrode are alternately sandwiched and stacked to form a zinc ion battery cell, in which the positive electrode size is a 30×40 mm square MnO2 electrode. The negative electrode size is the same as the positive electrode, the thickness of the negative electrode is 0.2 mm, and it is an electrode after the surface treatment of the pure zinc sheet. The separator is a composite film composed of a grafted polypropylene film and a non-woven fabric. The electrolyte of the battery is a mixed electrolyte containing 1.0M ZnSO4, 0.5M MnSO4 and additives, and its pH value is 4.5-5.0.
[0051] Example 1
[0052] Weigh 0.5g corn flour and 1.5g commercial electrolytic γ-MnO2 powder passed through a 400-mesh sieve, mix and stir the solid phase evenly, then transfer to a ceramic dry pot and place in a tubular furnace. The flowing atmosphere is oxygen at a flow rate of 60ml per minute. The first temperature rise interval is from room temperature to 180°C, and the heating rate is 5°C / minute. The second temperature rise interval is from 180°C to 300°C, with a heating rate of 0.2°C / minute, and the constant temperature time at 300°C is 2h. Then cool from the second temperature to room temperature, and the cooling rate is natural cooling. Oxygen is introduced into the reaction system to exhaust the gas during the entire treatment process. The obtained mixture is in powder form, and the XRD test results show that it is in the γ-phase, and its physical phase still maintains the original crystal structure, such as Figure 1 The carbon-coated MnO2 powder samples were observed by scanning electron microscopy, and four different regions (such as Figure 2 As shown), EDAX element spectrum analysis was performed, and the spectrum analysis results are shown in the figure Figure 3 , Figure 4 , Figure 5 , Figure 6 The proportion of manganese, oxygen and carbon on the edge of manganese dioxide particles is shown in Table 1. The results show that the surface of manganese dioxide particles after carbon coating contains rich carbon elements. EDAX analysis of the manganese dioxide particles after carbon coating showed that the carbon content was about 10%. Figure 7 shown.
[0053] Table 1 Percentage of elements in four selected areas of manganese dioxide particles
[0054]
[0055] Example 2
[0056] 1.0g corn flour and 1.5g electrolytic γ-MnO2 powder were weighed at a weight ratio of 10:15, and the solid-solid phases were evenly mixed and then transferred to a ceramic dry pot and placed in a tube furnace with a flowing atmosphere of nitrogen. The carbonization treatment includes a heating, constant temperature and cooling process. The heating rate and other conditions are consistent with those in Example 1. The mixture obtained after carbonization is in powder form. The sample was taken for XRD detection. The results showed that its crystal structure maintained the original γ-phase structure, such as Figure 8 shown.
[0057] Example 3
[0058] This example adopts a solution of carbonization in an air atmosphere of a muffle furnace after wet mixing of liquid and solid phases. Specifically, it includes: weighing 0.5g glucose and 1.5g water, dissolving the glucose in water first, then weighing 1.5g commercial electrolytic γ-MnO2 powder that has passed through a 400-mesh sieve, and then pouring 1.5g MnO2 into the glucose solution and mixing and stirring. The mixed solution is heated at 60°C to evaporate most of the water to a semi-solid state, and a portion is transferred to a ceramic dry pot and placed in a muffle furnace. The temperature is first raised to 180°C in the atmosphere at a heating rate of 5°C / minute. Then the temperature is raised to 300°C at a heating rate of 0.2°C / minute. Carbonization treatment is carried out at a constant temperature of 300°C for 2 hours, and then cooled to room temperature at a natural cooling rate. During the heating and constant temperature process, gas (air) flows naturally in and out of the reaction system. The obtained mixture is ground into a powder, and the XRD test results show that it is in the γ-phase, and its physical phase still maintains the original crystal structure, such as Figure 3 The other part is treated in the same way, except that the heating rate is adjusted to 1.2℃ / min in the second temperature range of 180-300℃. The samples were taken after carbonization treatment and analyzed by XRD. The results showed that the phase structure has changed from γ-MnO2 to Mn3O4 phase composition, such as Fig. 9 As shown in the middle curve B. It shows that the control of heating rate is very important.
[0059] Example 4
[0060] This embodiment adopts a carbonization scheme in an oxygen atmosphere of a tubular furnace after wet mixing of liquid and solid phases. Specifically, it includes: preparing two glucose aqueous solutions of 100g / L and 333g / L, that is, weighing 0.5g glucose and 5g distilled water and 0.5g glucose and 1.5g distilled water respectively. First, dissolve glucose in distilled water, then weigh 1.5g of each of two commercial electrolytic γ-MnO2 powders that have passed a 400-mesh sieve, and then pour MnO2 into the above two glucose concentration solutions and mix and stir. The mixture is heated at 60°C to evaporate most of the water to a semi-dry state, transferred to a ceramic dry pot and placed in a tubular furnace, and the flowing atmosphere is oxygen. The first temperature rise interval is from room temperature to 180°C, and the heating rate is 5°C / minute. The second temperature rise interval is from 180°C to 300°C, the heating rate is 0.2°C / minute, and the constant temperature time at 300°C is 2h. Then cool from the second temperature to room temperature, and the cooling rate is natural cooling. During the whole treatment process, oxygen was introduced to exhaust the reaction system. The obtained mixture was tested by XRD. The results showed that the two concentrations of glucose carbon source mixed with manganese dioxide liquid phase still maintained the original crystal structure after carbonization at low temperature of 300 degrees. Fig.10 After glucose and other carbon sources are carbonized at 300 degrees, there is only one peak at a diffraction angle of about 20 degrees, as shown in Fig.11 As shown. This indicates that the carbon source has been completely carbonized and its phase is amorphous carbon. The surface of the coated manganese dioxide particles is observed under an electron microscope to show an amorphous carbon structure, as shown Fig.12 As shown in the figure, the average carbon content measured by EDAX energy spectrum analysis is 8-10%.
[0061] Weigh 3g of carbon-coated γ-MnO2 powder, 0.375g of acetylene black and 2.81g of 4wt% carbon multi-walled nanotube aqueous solution, mix well and pour into a ball mill, then weigh and add 38g of ceramic balls for wet grinding, and ball mill at 300r / min for 10h. After most of the water in the obtained mixed slurry evaporates, add an appropriate amount of anhydrous ethanol and 0.44g of 60% PTFE suspension, and stir the slurry into a paste-like mud mass under constant stirring. The MnO2 paste mud mass is rolled into thin sheets on a biaxial rolling machine for multiple times, and a 904L stainless steel mesh prepared by pre-cleaning and degreasing is added and rolled together. Finally, the total thickness of the electrode is 0.5 mm. After completion, the electrode is placed in an 80℃ drying oven, and the MnO2 loading of the electrode is weighed after drying. The MnO2 loading is 40 mg / cm 2. MnO2 electrode is the positive electrode, pure zinc sheet with a thickness of 0.2 mm is the negative electrode, the positive electrode, separator and negative electrode are alternately sandwiched and stacked to form a zinc ion battery cell, the separator is a composite film composed of grafted polypropylene film and non-woven fabric, and the size of the positive and negative electrodes is 30×40 mm square electrode. The electrolyte of the battery is a mixed electrolyte of 1.0M ZnSO4, 0.5M MnSO4 and additives, with a pH of 5.0. The battery performance is measured by constant current charge and discharge (GCD) method. Fig.13 The figure is a comparison of the cycle stability of the MnO2 electrode after carbon coating treatment of the present invention and the MnO2 electrode without carbon coating. It can be seen that the cycle stability of the electrode is significantly improved after carbon coating of MnO2.
[0062] Example 5
[0063] Weigh 2g of citric acid and 2.7g of water, dissolve the citric acid in water first, then weigh 6.7g of commercial electrolytic γ-MnO2 powder that has passed through a 400-mesh sieve, then pour 6.7g of MnO2 into the citric acid solution and mix and stir. The mixed solution is heated at 80°C to evaporate most of the water to a semi-solid state, transferred to a ceramic dry pot and placed in a muffle furnace for carbonization heat treatment. The treatment process includes heating, constant temperature and cooling procedures. The first stage heating rate is 10°C / minute, and the temperature range is from room temperature to 180°C. The second stage temperature range is from 180°C to 300°C, the heating rate is 1°C / minute, and the constant temperature time is 3h. Finally, cool from the second stage temperature to room temperature, and the cooling rate is natural cooling. During the heating and constant temperature process, a natural air atmosphere flows in and out of the muffle furnace. The mixture after carbonization heat treatment is ground into powder, and the XRD analysis of the phase structure of MnO2 before and after heat treatment carbon coating is shown in the following figure. Fig.14 The results show that except for the diffraction peak at 20 degrees, which becomes wider and the relative intensity becomes weaker, the angles of the other diffraction peaks remain unchanged, and the peaks remain sharp and clear. The surface of the carbon-coated MnO2 particles was subjected to energy spectrum analysis. The results show that in addition to manganese and oxygen, the surface also contains carbon, such as Fig.15 Further EDAX energy spectrum analysis of the surface edge of the carbon-coated MnO2 particles showed that it only contained carbon elements, such as Fig.16 shown.
[0064] The MnO2 electrode was prepared in the same manner as in Example 4, with a loading of 45 mg / cm 2 The MnO2 electrode is used as the positive electrode, and the pure zinc sheet with a thickness of 0.2 mm is used as the negative electrode. The positive electrode, the separator and the negative electrode are alternately sandwiched and stacked to form a zinc ion battery cell. The separator is a composite film composed of a grafted polypropylene film and a non-woven fabric. The size of the positive and negative electrodes is a 30×40 mm square electrode. The electrolyte of the battery is a mixed electrolyte of 1.0M ZnSO4, 0.5M MnSO4 and additives, with a pH of 5.0. Fig.17The relationship between the discharge capacity and the number of cycles in the constant current charge and discharge test of the MnO2 electrode after carbon coating treatment of the present invention is shown in Figure 1. Compared with the cycle stability of the MnO2 electrode without carbon coating, the cycle stability of the MnO2 surface coated with carbon is significantly improved.
[0065] Example 6
[0066] According to the weight ratio of 5:15, 8g corn flour and 24g electrolytic γ-MnO2 powder passed through a 400-mesh sieve were weighed, the solid-solid phases were mixed and stirred evenly, then transferred to a ceramic dry pot and placed in a muffle furnace. The flowing atmosphere was air, and the muffle furnace atmosphere was evacuated and flowed during the heating and constant temperature process. The exhaust rate was 10 cubic meters per hour. The first heating range was from room temperature to 180°C, and the heating rate was 5°C / minute. The second heating range was from 180°C to 300°C, with a heating rate of 0.1°C / minute, and the constant temperature time at 300°C was 2h. Then it was cooled from the second temperature to room temperature, and the cooling rate was natural cooling. The obtained mixture was in powder form, and the XRD test results showed that it was in the γ-phase, and its physical phase still maintained the original crystal structure, such as Fig.18 shown.
[0067] Example 7
[0068] According to the weight ratio of 5:15, 0.5g starch and 1.5g electrolytic γ-MnO2 powder passed through a 400-mesh sieve were weighed, the solid-solid phases were mixed and stirred evenly, and then transferred to a ceramic dry pot and placed in a tubular furnace with an oxygen flowing atmosphere. During the heating and constant temperature treatment process, the air intake flow of the reaction system was controlled at a flow rate of 60ml / min. The heating rate, heating range, constant temperature time and cooling procedure of the carbonization treatment were consistent with those of Example 1. The mixture obtained after carbonization was in powder form. The sample was taken for XRD detection, and the results showed that its physical phase still maintained the original γ-MnO2 phase structure, such as Fig.19 shown.
[0069] Example 8
[0070] According to the weight ratio of 5:15, 0.5g starch and 1.5g electrolytic γ-MnO2 powder through a 400-mesh sieve were weighed, the solid-solid phases were mixed and stirred evenly, and then transferred to a ceramic dry pot and placed in a tube furnace with an oxygen flowing atmosphere. The second stage of the carbonization treatment was heated at a rate of 1.5°C / min, and the other conditions were the same as those of Examples 1 and 7, that is, compared with Example 7, only the heating rate in the second stage was different. The mixture obtained after carbonization was in powder form. The sample was taken for XRD testing, and the results showed that its phase had changed, and the structure had changed from γ-MnO2 to M3O4, such as Fig. 20 The corresponding electrode electrochemical cycle performance is shown in Fig.21 shown.
[0071] The above-described embodiments are only some of the preferred solutions of the present invention, but they are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing low-temperature carbon-coated γ-MnO2, characterized in that: These include: Mixing γ-MnO2 powder and an organic carbon source compound; the organic carbon source compound is one or more of corn flour, starch, citric acid, and glucose; The obtained mixed material is subjected to two-stage temperature rising treatment. The first stage of temperature rising is controlled at a temperature range from room temperature to T1, where T1 is 180-200°C. The second stage of temperature rising is controlled at a rate of 0.1-1.0°C / min, and the temperature range is from T1 to T2, where T2 is 280-320°C. The mixed material is subjected to a constant temperature treatment at T2 for 1-3 hours, and then naturally cooled to room temperature to obtain carbon-coated MnO2, wherein the MnO2 is γ-phase.
2. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 1, characterized in that: The weight ratio of the organic carbon source compound to the γ-MnO2 powder is 1-10:
15.
3. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 1, characterized in that: The mixing is solid-solid mixing or liquid-solid mixing. The liquid-solid mixing is to take the organic carbon source compound and γ-MnO2 powder into distilled water, mix and stir evenly, and then evaporate the water to a semi-dry state or a dry solid state.
4. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 1, characterized in that: The obtained mixed material is first transferred into a ceramic crucible, and the ceramic crucible is placed in a tube furnace or a muffle furnace for two-stage temperature increase treatment.
5. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 4, characterized in that: The atmosphere in the tubular furnace is oxygen or nitrogen with a flow rate of 20-100 ml / min, the atmosphere in the muffle furnace is air, the openings are open for inlet and outlet air flow, and the tubular furnace and the muffle furnace have an exhaust system.
6. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 1, characterized in that: During the second temperature rising process and / or the constant temperature treatment process, the reaction system is evacuated or exhausted.
7. The method for preparing low-temperature carbon-coated γ-MnO2 according to claim 1, characterized in that: The second stage heating rate is 0.1-0.5°C / min.
8. A MnO2 electrode slurry, characterized in that: Contains carbon-coated MnO2 prepared by the method according to any one of claims 1 to 7.
9. An aqueous zinc ion battery, characterized in that: The positive electrode is prepared using the electrode slurry as claimed in claim 8.
Citation Information
Patent Citations
Preparation method of porous carbon coated MnO nanocrystalline composite material and application of porous carbon coated MnO nanocrystalline composite material in lithium battery
CN107394183A
AU4258868A